OVERVIEW OF CHANGING EATING PATTERNS AND THE ASSOCIATION WITH GENDER IN ADOLESCENT ATHLETES IN STUDENT-ATHLETE TRAINING CENTRE DKI JAKARTA DURING COVID-19 - Hardiyanti, Marina; Penggalih , Mirza Hapsari Sakti Titis; Solichah, Kurnia Maratus; Niamilah, Ibtidau; Bactiar, Nia; Syarifah, Naila Alfi; Arini, Ni Putu Dewi; Listianto, Akbar Ramdan; Adinda, Dian (Media Gizi Indonesia, 2025)
Athletes are a group that has experienced changes, especially regarding their eating patterns and physical activities, during Covid-19. Several studies have found changes in eating patterns, particularly in the frequency and types of food consumed, among adolescent athletes during Covid-19. A study showed that changes in eating patterns during the isolation of the pandemic influenced female athletes more than males. Female athletes found challenges in fulfilling energy needs and fighting with their body image. However, their adherence and awareness to consuming healthy food are better than male athletes. Based on the background, this research aims to explore the overview of changes in eating patterns and the relations with gender among adolescent athletes in Indonesia who train at the Student Sports Training Center (PPOP) during Covid-19. This study is an observational study with a cross-sectional design. The study subjects were 139 athletes from six sports groups and 25 sports branches conducted in July-August 2021. Data collection was done through online questionnaires via Google Forms consisting of questions regarding changes in eating patterns, amount of food intake, types of food consumed, methods of food preparation, quality of food consumed, and frequency of meals per day. This study obtained ethical approval with the number KE/1174/11/2021. Through data analysis using the Chi-square test, it was found that there was no statistical association between gender and changes in eating pattern variables of adolescent athletes in PPOP DKI Jakarta during Covid-19.